Advice given to patients with epistaxis by A&E doctors. Issue 10 (27th September 2005) - Eze, N; Lo, S; Toma, A
Abstract : This study was devised to determine the proportion of patients with epistaxis seen in accident and emergency (A&E) departments and discharged with verbal/written advice, and to examine if this information affects re-attendance rates. A questionnaire was given to all A&E doctors probing their current practice regarding advice given to patients with epistaxis on discharge. The information was complemented with a case note audit of patients with epistaxis seen and discharged by A&E doctors over a 2 month period, which assessed the content and format of advice given and the number of re-attendances. The standard used stated that all patients discharged from A&E should be given both verbal and written advice regarding the prevention and management of further bleeds. The A&E doctors were then invited to a presentation on the management of epistaxis and the appropriate advice to give patients on discharge. Written advice leaflets on the prevention and management of further bleeds were placed in the A&E department and were accessible to doctors and patients. Case notes were re-audited over the following 2 month period. Verbal and written advice increased from 19% to 61% and 2% to 54% respectively. The number of re-attenders who had previously only seen A&E doctors was reduced from 11 (17%) in the first half to 5 (8%) in the second half of the cycle, representing a 9% reduction. We conclude that the provision of adequate verbal and written advice to patients with epistaxis may have an important role in the prevention of further bleeds and subsequent re-attendance to A&E departments.